Service Learning: An Example of Experiential Education in the Area of Taxation Law - Michael Blissenden (Legal Education Review)
At its best, clinical legal education exposes law teachers and students to the complexity of responding to clients’ legal issues. The development of holistic, skilled and ethical student responses to clients’ casework issues is of course an appropriate objective of a law school clinical program. Beyond this, it is also possible to look behind individual clients’ problems at the common social factors contributing to their difficulties. Students who examine these “systemic” issues in their clients’ lives seem to develop a more comprehensive understanding of the legal issues confronting their clients individually and as members of a group. Some clients who are encouraged to see their problems as a part of a wider social context also become active in the political process in order to try and improve their own circumstances and those of others. Law teachers who facilitate the exposure of their students and clients to the relationship between individual and collective social problems also benefit. They mature in the depth of their appreciation of substantive law reform.